Cystectomy for obstructive uropathy secondary to lupus cystitis: a learning point for urologists?. (January 2014) - De Siqueira, J; Mangera, A; Venugopal, S; Edhem, I
We present the case of a 72-year-old woman with obstructive uropathy secondary to interstitial cystitis-like pathology as the presenting features of systemic lupus erythematosus (SLE). After her initial presentation with visible haematuria, she was shown to have hydroureteronephrosis and a bulky bladder mass. Histology of bladder biopsies demonstrated severe inflammation. Following unsuccessful attempts to stent the ureters, worsening renal function and a concern regarding possible malignancy, a cystectomy and ileal conduit were performed. Final histology showed her bladder had only benign inflammatory changes. Subsequent investigations led to a diagnosis of SLE. We suggest that in cases of obstructive uropathy in association with severe inflammation of the bladder, lupus cystitis should be considered at an early stage and managed with steroids in the first instance. This may lead to resolution of the underlying pathology and thus avoid the need for urinary diversion and cystectomy.